The Finite-Difference Model of Fully Saturated Groundwater Contaminant Transport - Purnaditya, NgakanPutu; Soeryantono, Herr; Marthanty, Dwinanti Rika; Sjah, Jessica (International Journal of Engineering and Technology, 2018)
Groundwater quality is one of water resource problem. This problem is driven by contaminant transport phenomena and can be described as a mathematical model. Contaminant transports equation usually is composed by advection and dispersion flux. In the porous medium or aquifer, contaminant meet tortuosity effect, therefore hydrodynamic dispersion must be considered as the development of dispersion flux. This paper explains the mathematical model of groundwater contaminant on fully saturated condition. It starts from governing equation of contaminant transport. Advection flux is based on groundwater velocity. In steady state condition, groundwater velocity can be determined as certain value. In another hand, in the transient condition, groundwater velocity must be determined based on the solution of groundwater flow model. Dispersion flux is calculated through first Fick’s law and this component is distinguished into two parts follow mechanical dispersion and molecular diffusion. Mechanical dispersion affected by groundwater velocity and dispersivity. Contaminant transport equation is solved numerically using Finite Difference Method (FDM). This final model is validated theoretically and then this model is simulated into transient condition. The result of the simulation is described and explained graphically. Based on this research, the result of FDM model has similar physical behavior to FEM model from CTRAN example.